Hybrid acousto-nano-biosensor - Kolesov, Vladimir V; Anisimkin, Vladimir V; Kuznetsova, Iren E; Soldatov, Eugenii S; Dagesyan, Sarkis A; Melnikov, Alexander E; Kashin, Vadim V; Smirnov, Andrey V (SPIE, 2019)
The technology realizing two multi-scale structures on piezoelectric single crystal lithium niobate plate was developed. The system of interdigital electrodes for the acoustic delay line operating at the range 2-3 MHz was produced by using photolithography. This delay line was combined with the nanotransduces having size about 60-80 nm. These transducers were produced by using negative electron-beam nanolithography.